Rozwiąż równanie.
(2x^3+5)(2x-5x^3)=0


Odpowiedź :

Odpowiedź:

x∈{ -∛ 2,5;  - √0,4; √0,4 }

Szczegółowe wyjaśnienie:

(2x³ +5)(2x - 5x³ )=0

2x³ + 5 = 0  /-5                 ∨      2x - 5x³ =0

2x³ = -5  /:2                                     x(  2 -5x² )=0

x³ = -2,5                                             x = 0 ∨ 2-5x²=0 /:(-1)

x= ∛ -2,5                                                         5x² -2=0/ :5

x= ∛{(-1)· 2,5}                                                    x² - 0,4=0

x= -∛2,5                                                         (x- √0,4)(x+√0,4)=0

                                                                         x- √0,4 =0 ∨ x +√0,4=0

 a²-b²= (a-b)(a+b)                                                           x= √0,4 ∨  x= - √0,4